A practical approach for PD-L1 evaluation in gastroesophageal cancer - Angerilli*, Valentina; Fassan*, Matteo; Parente, Paola; Gullo, Irene; Campora, Michela; Rossi, Chiara; Sacramento, Maria Luisa; Pennelli, Gianmaria; Vanoli, Alessandro; Grillo*, Federica; Mastracci*, Luca (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
PD-L1 is an established predictive immunohistochemical biomarker of response to immune checkpoint inhibitors. At present, PD-L1 is routinely assessed on biopsy samples of advanced gastroesophageal cancer patients before initiating first-line treatment. How-ever, PD-L1 is still a suboptimal biomarker, due to changing cut-off values and scoring systems, interobserver and interlaboratory variability.This practical illustrated review discusses the range of staining patterns of PD-L1 and the potential pitfalls and challenges that can be encountered when evaluating PD-L1, focusing on gastric and gastroesophageal adenocarcinoma (G/GEA) and esophageal squamous cell carcinoma (ESCC).[read more]